2012
DOI: 10.1111/j.1365-2184.2012.00834.x
|View full text |Cite
|
Sign up to set email alerts
|

Analogous effects of recombinant human full‐length amelogenin expressed by Pichia pastoris yeast and enamel matrix derivative in vitro

Abstract: rHhAm175 modulated cell activities of human PDLFs, to a comparable extent as porcine EMD. These data suggest that rHhAm175 might be used to induce periodontal tissue regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Amelogenins enhance the proliferation and differentiation of periodontal ligament cells, the proliferation, adhesion and migration of several types of periodontal cells and the differentiation of osteoblasts. Amelogenins are also involved in the regeneration of alveolar bone and/or periodontal ligament cells . However, the mechanisms underlying these processes remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amelogenins enhance the proliferation and differentiation of periodontal ligament cells, the proliferation, adhesion and migration of several types of periodontal cells and the differentiation of osteoblasts. Amelogenins are also involved in the regeneration of alveolar bone and/or periodontal ligament cells . However, the mechanisms underlying these processes remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…regeneration of alveolar bone and/or periodontal ligament cells (15,18,43,44). However, the mechanisms underlying these processes remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Grp78 overexpression together with amelogenin treatment activates Rac1-GTP. With regard to amelogenin treatment, the effect on cell viability or differentiation seems to depend on the cell differentiation state (Zeichner-David, 2006;Cheng et al, 2012). The bands are representative of three independent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have established that multifunctional ECM proteins regulate cell behavior (Rozario et al, 2010;Ravindran et al, 2014), and that modulated stem cell migration contributes to the initial process of tissue regeneration (Sonoyama et al, 2006). While the cellular responses to amelogenin, an ECM-biocompatible protein, in PDL fibroblasts have been examined Cheng et al, 2012), the key signaling molecules and effects on PDLSCs have yet be completely defined. Therefore, we examined the biological interaction between amelogenin and Grp78 in The effect of Grp78 and rM180 on proliferation of 1-17 cells was measured using a WST-8 assay.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al suggested that human recombinant amelogenin promotes proliferation and migration of human periodontal ligament cells to an extent comparable with that of EMD via ERK signaling. 45 Previously, it was revealed that rh174, an amelogenin cleavage product lacking the N-terminus (rh128), and the C-terminal region of rh174 enhance the proliferation and mineralization of human cementoblast-lineage cells compared with control groups. On the other hand, no obvious difference was observed in proliferation or mineralization following treatment with cleavage products lacking the Cterminus (rh163) compared with control groups.…”
Section: F I G U R E 4 Effects Of Lamp1 Blockade On the Enhancement Omentioning
confidence: 99%